Effect of on Performing Loans (NPL), Loan to Deposit Ratio (LDR) and Operational Income Operating Costs (BOPO) on Return on Equity (ROE) PT. XDS Tbk Period 2011-2019 - Taufiq Supriadi; Juska Meidy Enyke Sjam (Institute of Computer Science (IOCS), 2021)
The banking sector is one of the important sectors in the Indonesian economy. Considering that its function as an intermediary institution and payment transaction organizer also functions in collecting funds from the public and channeling them back in the form of credit, it can be said that banking is one of the sectors that plays a role in driving the economy. To maintain public trust, the bank must maintain its liquidity and operate effectively and efficiently to achieve high profitability. This study aims to determine the effect of Non Performing Loans (NPL), Loan to Deposit Ratio (LDR) and Operational Income Operating Costs (BOPO) on Return on Equity (ROE) at Bank Mandiri, Tbk for the 2011-2019 period. This research was conducted with descriptive analysis with a quantitative approach. The results showed that NPL, LDR and BOPO partially and simultaneously had a significant effect on ROE at PT. XDS for the period 2011-2019